Medullary thyroid cancer in combination with autoimmune thyroiditis after COVID-19 - E. V. Ryabchenko (Сибирский онкологический журнал)
Background. Coronavirus disease 2019 (COVID-19) is a pandemic of the new millennium. COVID-19 can cause both pulmonary and systemic infammation, and can rapidly progress to multiple organ failure. Data on the relationship between COVID-19 and the thyroid gland have been available since March 2020. The thyroid gland and viral infection as well as associated infammatory-immune reactions participate in a complex interaction. The most common autoimmune disease is chronic autoimmune thyroiditis (chronic lymphocytic thyroiditis, Hashimoto thyroiditis). The majority of medullary thyroid cancers present as a thyroid nodule. Cervical lymph nodes and distant metastases are often detected at the time of diagnosis. The development of autoantibodies may be part of a more complex protective antitumor mechanism, the purpose of which is to eliminate the precursors of future tumor cells.The purpose of the study was to describe a clinical case of diagnosing medullary thyroid cancer in the patient who had COVID-19.Case description. We present the case of a 43-year-old woman who had coronavirus pneumonia (COVID-19), which was accompanied by an increase in serum procalcitonin (PC) level, which required additional examination. Since 2020, she had been observed for autoimmune thyroiditis, which was manifested by a thyroid nodular of a small size. After discharge from the COVID hospital, an ultrasound examination of the thyroid gland revealed an increase in the left lobe thyroid nodule up to 15 mm. The level of calcitonin was 681 pg/ml. Fine needle aspiration (FNA) biopsy of the thyroid gland showed suspicion for medullary thyroid cancer. Thyroidectomy with central lymph node dissection (level VI) was performed. A planned histological examination of the surgical specimen confrmed medullary thyroid cancer.Conclusion. In the present clinical case, medullary thyroid cancer was detected in the patient who had COVID-19 with elevated PC level, which was the basis for a diagnostic search.